A pachyman tri-terpenoid modified product with stage-specific repair function-sodium alginate hydrogel dressing and its preparation method and application
Patent Information
- Application Number
- CN202610307539.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-13
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-03-13
AI Technical Summary
然而,将茯苓皮三萜直接应用于外用敷料面临两大关键技术瓶颈:第一,溶解性壁垒
[0005]本发明相对于现有技术具有以下有益效果:本发明通过固体分散技术(以聚乙烯吡咯烷酮K30为载体,药载质量比1:4~1:12)或成盐技术对其进行物理化学改性,获得不同改性路径获得的三种茯苓皮三萜差异化改性产物(PCTT/SD、PCNT/SD、PCWT),再与海藻酸钠溶液经钙离子交联复合,构建了系列复合水凝胶敷料;在体内复杂的伤口愈合模型中,并非表现出相似或模糊的促愈效果,而是展现出清晰、分化且互补的“阶段特异性修复功能”。这一发现构成了本发明的核心创造性,具体表现为:
Smart Images

Figure CN121971377B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, and in particular to a method for preparing and applying a sodium alginate hydrogel dressing, a modified product of Poria cocos peel triterpenoids. Background Technology
[0002] Skin wound healing is a highly ordered and complex biological process, classically divided into the hemostatic phase, inflammatory phase, proliferative phase, and remodeling phase. Ideal wound dressings should not only provide a moist healing environment, absorb exudate, and protect the wound surface, but also actively intervene in and promote this dynamic repair process. Hydrogels, due to their high water content, good biocompatibility, and three-dimensional network structure similar to the extracellular matrix, have become ideal matrices for modern wound care dressings. Among them, sodium alginate (SA), as a natural anionic polysaccharide, can form hydrogels through mild cross-linking with divalent cations. It is highly safe, widely available, and has mature applications in the dressing field. Meanwhile, searching for components with multi-target repair activities from traditional Chinese medicine is a research hotspot in wound treatment. The dried sclerotium peel of Poria cocos (i.e., "Poria peel") is a major byproduct of its processing and is often discarded. Modern research shows that Poria peel is rich in triterpenoids (such as pachymic acid and dehydrotomonic acid), possessing significant anti-inflammatory, antioxidant, and fibroblast proliferation-promoting and collagen synthesis-enhancing pharmacological activities, demonstrating great potential for wound treatment. However, directly applying Poria cocos peel triterpenes to topical dressings faces two major technical bottlenecks: First, the solubility barrier. Poria cocos peel triterpenoids are highly hydrophobic, making it difficult to disperse directly and uniformly in hydrophilic hydrogel networks. This results in low loading rates, uneven distribution, burst release, or incomplete release, severely impacting bioavailability and efficacy. Second, the issue of singular efficacy and temporal matching. Wound healing is dynamic, requiring different pharmacological focuses at different stages (e.g., anti-inflammatory in the early stage, collagen synthesis promotion in the middle stage, and epithelial regeneration and tissue remodeling promotion in the later stage). While simple triterpenoid extracts or mixtures may possess multiple activities, they cannot achieve precise, sequential regulation of different healing stages over time, thus limiting efficacy. Summary of the Invention
[0003] To address the aforementioned technical deficiencies, this invention provides the following technical solution: This invention provides a poria cocos peel triterpenoid modified product—sodium alginate hydrogel dressing—with stage-specific repair function, comprising: a sodium alginate hydrogel matrix with a three-dimensional porous network structure, and a poria cocos peel triterpenoid differentiated modified product dispersed in the sodium alginate hydrogel matrix; the poria cocos peel triterpenoid differentiated modified product is selected from at least one of the following: a poria cocos peel total triterpenoid solid dispersion with polyvinylpyrrolidone as a carrier, a poria cocos peel neutral triterpenoid solid dispersion with polyvinylpyrrolidone as a carrier, and poria cocos peel triterpenic acid salt.
[0004] The present invention also provides the application of the modified poria cocos peel triterpenoid product-sodium alginate hydrogel dressing or the poria cocos peel triterpenoid product-sodium alginate hydrogel dressing prepared by the preparation method described above in the preparation of a drug for promoting skin wound healing.
[0005] This invention offers the following advantages over existing technologies: By employing solid dispersion technology (using polyvinylpyrrolidone K30 as a carrier, with a drug-to-carrier mass ratio of 1:4 to 1:12) or salt formation technology to physicochemically modify Poria cocos peel, three differentiated modified products (PCTT / SD, PCNT / SD, PCWT) obtained through different modification pathways are constructed. These products are then cross-linked with sodium alginate solution via calcium ions to create a series of composite hydrogel dressings. In complex in vivo wound healing models, these dressings do not exhibit similar or ambiguous healing-promoting effects, but rather demonstrate clear, differentiated, and complementary "stage-specific repair functions." This discovery constitutes the core inventiveness of this invention, specifically manifested as follows:
[0006] 1. Differentiation of therapeutic effects in the early stage: The hydrogel dressing (PCNT / SD / Gel) containing neutral triterpenoid solid dispersion of Poria cocos peel showed the strongest anti-inflammatory activity in the early stage of healing (0-5 days), which can rapidly inhibit inflammatory factors (such as IL-6, TNF-α), reduce redness and swelling exudation, and promote the formation of initial scab.
[0007] 2. Differentiation of therapeutic effects in stages (mid-stage): The hydrogel dressing containing the total triterpenoids of Poria cocos peel (PCTT / SD / Gel) showed the best ability to promote collagen synthesis and deposition in the mid-stage of healing (5-10 days), significantly upregulated COL1α2 gene expression, made the granulation tissue fuller and the collagen fiber arrangement denser.
[0008] 3. Differentiation of therapeutic effects in the later stages: The hydrogel dressing containing Poria cocos peel triterpene salts (PCWT / Gel) drives efficient epithelialization, angiogenesis and tissue remodeling in the later stages of healing (7-14 days), significantly promotes the expression of growth factors such as EGF and VEGF, and is accompanied by significant regeneration of skin appendages (such as hair follicles), ultimately achieving healing with less scarring and higher quality. Attached Figure Description
[0009] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0010] Figure 1 This is a schematic diagram illustrating the extraction of triterpenoid components from Poria cocos peel, the preparation of a modified product of Poria cocos peel—sodium alginate hydrogel dressing, and its role in promoting wound healing.
[0011] Figure 2pH change curve during the salt formation reaction of total terpenoids (PCTT) in Poria cocos peel with NaOH, full-wavelength absorption spectrum of ursolic acid (UA) methanol solution, standard curve of ursolic acid concentration and absorbance, and standard curve of resveratrol concentration and absorbance.
[0012] Figure 3 The FT-IR spectra of PCTT, PCNT, and PCWT prepared in Examples 1-2 are shown.
[0013] Figure 4 FT-IR spectra of PVP K30, PCTT, PCTT / SD, PCTT+PVP K30 physical mixture, Res, Res / SD and Res+PVPK30 physical mixture;
[0014] Figure 5 XRD patterns of PVP K30, PCTT, PCTT / SD, PCTT+PVP K30 physical mixture, Res, Res / SD and Res+PVPK30 physical mixture;
[0015] Figure 6 The image is a scanning electron microscope (SEM) image of PCNT / SD in Example 3;
[0016] Figure 7 This is a scanning electron microscope image of the PCTT / SD / Gel in Example 4;
[0017] Figure 8 This is a scanning electron microscope image of PCNT / SD / Gel in Example 4;
[0018] Figure 9 This is a scanning electron microscope image of the PCWT / Gel in Example 4;
[0019] Figure 10 Fourier transform infrared (FT-IR) spectra and water content of SA, Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel and PCWT / Gel;
[0020] Figure 11 Visual observation of the color of the supernatant after hemolysis tests of different hydrogel dressings and quantitative analysis of the hemolysis rate;
[0021] Figure 12 Swelling rate of different hydrogel dressings in PBS over 72 h;
[0022] Figure 13 The middle section shows the frequency dependence curves of storage modulus (G') and loss modulus (G") of Gel, triterpenoid drug-loaded hydrogel, and Res / SD / Gel systems.
[0023] Figure 14 The change in body weight of rats in each group within 10 days after wound formation;
[0024] Figure 15 In the middle A~B, the spleen index and thymus index of rats are on day 10 after wound formation;
[0025] Figure 16 Representative images of wound healing at different time points in a full-thickness skin defect model;
[0026] Figure 17 The wound contraction rate at different time points for different treatment groups;
[0027] Figure 18 Image A shows H&E staining of wound tissue on days 3, 7, and 10 after drug administration (scale bar: 100 μm); Image B shows Masson trichrome staining of wound tissue on days 3, 7, and 10 after drug administration.
[0028] Figure 19 The results of ELISA for the level of interleukin-10 (IL-10) in wound tissue on day 10;
[0029] Figure 20 B represents the relative mRNA expression level of tumor necrosis factor-α (TNF-α) in wound tissue on day 10;
[0030] Figure 21 The relative mRNA expression level of EGF in wound tissue on day 10;
[0031] Figure 22 The relative mRNA expression levels of VEGF and FGF-2 in wound tissue on day 10. Detailed Implementation
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0033] This application provides a modified product of Poria cocos peel triterpenes with stage-specific repair function - sodium alginate hydrogel dressing, comprising: a sodium alginate hydrogel matrix with a three-dimensional porous network structure, and a differentiated modified product of Poria cocos peel triterpenes dispersed in the sodium alginate hydrogel matrix; the differentiated modified product of Poria cocos peel triterpenes is selected from at least one of the following: a solid dispersion of total triterpenes of Poria cocos peel with polyvinylpyrrolidone as a carrier, a solid dispersion of neutral triterpenes of Poria cocos peel with polyvinylpyrrolidone as a carrier, and a triterpene acid salt of Poria cocos peel.
[0034] This invention targets the specific active substance, Poria cocos peel triterpenes. By selecting specific modification pathways (such as using a solid dispersion of polyvinylpyrrolidone as a specific carrier, or a specific salt-forming reaction), it not only solves the problems of loading and release in hydrophilic gels, but also unexpectedly endows the final product with a clear and complementary "stage-specific repair function." That is, different modified products will autonomously and differentially act on different stages in the complex in vivo healing process, forming a "1+1+1>3" time-sequential synergistic therapeutic effect. Specifically, through in-depth research, the inventors unexpectedly discovered that the three differentiated modified products of Poria cocos peel triterpenes obtained by using different physicochemical modification pathways, when loaded into the same sodium alginate hydrogel system, do not exhibit similar or vague healing-promoting effects in a complex in vivo wound healing model, but rather show clear, differentiated, and complementary "stage-specific repair functions." This discovery constitutes the core inventiveness of this invention, specifically manifested as follows:
[0035] 1. Differentiation of therapeutic effects in the early stage: The hydrogel dressing (PCNT / SD / Gel) containing neutral triterpenoid solid dispersion of Poria cocos peel with polyvinylpyrrolidone as carrier showed the strongest anti-inflammatory activity in the early stage of healing (0-5 days), which can rapidly inhibit inflammatory factors (such as IL-6, TNF-α), reduce redness and swelling exudation, and promote the formation of initial scab.
[0036] 2. Differentiation of therapeutic effects in the middle stage: The hydrogel dressing (PCTT / SD / Gel) containing total triterpenoids of Poria cocos peel solid dispersion with polyvinylpyrrolidone as carrier showed the best ability to promote collagen synthesis and deposition in the middle stage of healing (5-10 days), significantly upregulated COL1α2 gene expression, made the granulation tissue fuller and the collagen fiber arrangement denser.
[0037] 3. Differentiation of therapeutic effects in the later stages: The hydrogel dressing containing Poria cocos peel triterpene salts (PCWT / Gel) drives efficient epithelialization, angiogenesis and tissue remodeling in the later stages of healing (7-14 days), significantly promotes the expression of growth factors such as EGF and VEGF, and is accompanied by significant regeneration of skin appendages (such as hair follicles), ultimately achieving healing with less scarring and higher quality.
[0038] Compared with existing single-function dressings or simple mixed drug-loaded dressings, the three modified hydrogel products of this invention have significant therapeutic advantages at different healing stages. Their synergistic and precise timing regulation effect makes the wound healing speed and healing quality superior to existing technologies.
[0039] In some embodiments, the method for preparing the solid dispersion of total triterpenoids from Poria cocos peel using polyvinylpyrrolidone as a carrier is as follows:
[0040] S1. After mixing Poria cocos peel with alcohol, heat and reflux to extract, and then concentrate and dry the extract to obtain total triterpenoids (PCTT) from Poria cocos peel. Specifically, the alcohol can be ethanol, which is an aqueous solution with a volume concentration of 70-80%. The reflux extraction temperature is 20-100℃ and the time is 1-3h. In the step of mixing Poria cocos peel with alcohol, the mass-volume ratio of Poria cocos peel to alcohol is 1g:(8-10)mL.
[0041] S2. After mixing the total triterpenoids of Poria cocos peel with polyvinylpyrrolidone (specifically polyvinylpyrrolidone K30 (PVPK30)), an alcohol solvent is added, and the mixture is continued to be mixed. After heating to evaporate the alcohol solvent, the mixture is dried to obtain a solid dispersion of total triterpenoids of Poria cocos peel with polyvinylpyrrolidone as the carrier. The alcohol solvent can be ethanol.
[0042] In some embodiments, the method for preparing a neutral triterpenoid solid dispersion of Poria cocos peel using polyvinylpyrrolidone as a carrier is as follows:
[0043] S1. The alcoholic solution of total triterpenoids from Poria cocos peel is added dropwise to an aqueous solution of alkali metal hydroxide. The reaction proceeds, and the alcohol is removed by vacuum distillation to obtain a concentrated aqueous solution. Specifically, the preparation method for the alcoholic solution of total triterpenoids from Poria cocos peel is as follows: The total triterpenoids from Poria cocos peel are added to an alcohol solvent (ethanol) to obtain an alcoholic solution of total triterpenoids from Poria cocos peel, wherein the mass-to-volume ratio of total triterpenoids from Poria cocos peel to alcohol is (3~4) g: 20 mL; the alcoholic solution of total triterpenoids from Poria cocos peel is added dropwise at 1~2 mL / min to an aqueous solution of alkali metal hydroxide at a temperature of 80~85℃. After the addition is complete, the reaction is continued with stirring for 2~3 h. The alcohol is removed by vacuum distillation to obtain a concentrated aqueous solution; the concentration of the aqueous solution of alkali metal hydroxide is 0.015~0.02 mol / L; the volume ratio of the alcoholic solution of total triterpenoids from Poria cocos peel to the aqueous solution of alkali metal hydroxide is 20:(400~410).
[0044] S2. After filtering the concentrated aqueous solution, the precipitate is obtained. The precipitate is the neutral triterpenoid compound (PCNT) of Poria cocos peel.
[0045] S3. After mixing the neutral triterpenoids from Poria cocos peel with polyvinylpyrrolidone, add an alcohol solvent, continue mixing, heat to evaporate the alcohol solvent, and then dry to obtain a solid dispersion of neutral triterpenoids from Poria cocos peel with polyvinylpyrrolidone as the carrier.
[0046] In some embodiments, the preparation method of Poria cocos peel triterpene salts is as follows:
[0047] S1. Add the alcoholic solution of total triterpenoids from Poria cocos peel dropwise to an aqueous solution of alkali metal hydroxide, react, remove the alcohol by vacuum distillation, and obtain a concentrated aqueous solution.
[0048] S2. Filter the concentrated aqueous solution and collect the filtrate. Concentrate the filtrate and dry it to obtain Poria cocos peel triterpene salt (PCWT). Poria cocos peel triterpene salt is a water-soluble carboxylate salt formed by the reaction of total triterpenoids in Poria cocos peel with alkali metal hydroxide.
[0049] In some embodiments, the mass ratio of total triterpenoids in Poria cocos peel to polyvinylpyrrolidone in the solid dispersion of total triterpenoids carried by polyvinylpyrrolidone is 1:(4~12). This ratio range can significantly improve the hydrophilicity and dispersion uniformity of the triterpenoids in Poria cocos peel. Preferably, the mass ratio is 1:9. In the solid dispersion of neutral triterpenoids in Poria cocos peel carried by polyvinylpyrrolidone, the mass ratio of neutral triterpenoids in Poria cocos peel to polyvinylpyrrolidone is 1:(4~12). Preferably, the mass ratio is 1:9. Under this ratio, the drug dissolution rate, hydrogel mechanical strength and drug release rate of the solid dispersion reach the optimal balance.
[0050] In some embodiments, the sodium alginate hydrogel matrix is cross-linked from sodium alginate, a calcium ion source, and D-gluconic acid-δ-lactone. A preferred cross-linking system is calcium carbonate (CaCO3) and D-gluconic acid-δ-lactone (GDL, chemical formula C6H2O). 10 The combination of O6 (CAS Registry No. 90-80-2) and D-gluconic acid-δ-lactone can slowly hydrolyze to release hydrogen ions. GDL slowly hydrolyzes in aqueous solution to produce gluconic acid and H+. + H + It reacts with CaCO3 to continuously and uniformly release Ca. 2+ This allows for gentle and deep cross-linking, forming a stable three-dimensional network.
[0051] In some embodiments, the calcium ion source is calcium carbonate; the mass ratio of D-glucono-δ-lactone to calcium carbonate is 3:2, which can achieve mild cross-linking and avoid uneven hydrogel network structure.
[0052] The alkali metal hydroxide is sodium hydroxide, and this reaction can increase the water solubility of Poria cocos peel triterpenes by more than 50%.
[0053] The modified product of Poria cocos peel - sodium alginate hydrogel dressing of the present invention has a water content of not less than 90% (which can maintain a moist healing environment for the wound), an equilibrium swelling rate of not less than 600% in 37°C and phosphate buffer (pH 7.4) (which can efficiently absorb wound exudate), and an in vitro hemolysis rate of less than 5% (which meets the blood compatibility safety standards for medical devices).
[0054] Based on the same inventive concept, this invention also provides a method for preparing the above-mentioned modified product of Poria cocos peel triterpenoids with stage-specific repair function - sodium alginate hydrogel dressing, comprising the following steps:
[0055] S1. Preparation of pregel solution: Dissolve sodium alginate in water to form a solution, add calcium ion source, and stir at 50°C for 30 minutes to disperse evenly to obtain pregel solution;
[0056] S2, Drug loading and cross-linking: Add the differentiated modified product of Poria cocos peel triterpenoid to the pregel solution in S1, stir, add D-gluconic acid-δ-lactone, continue stirring, degas for 10 minutes to remove bubbles, and obtain the mixture.
[0057] S3. Place the mixture in a mold and allow it to stand at room temperature (20~25℃) for 1 hour for cross-linking to form a poria cocos peel triterpenoid modified product - sodium alginate hydrogel dressing.
[0058] In some embodiments, sodium alginate is dissolved in water to form a sodium alginate solution, wherein the mass fraction of the sodium alginate solution is 1-5%.
[0059] The volume-to-mass ratio of sodium alginate solution, calcium ion source, differentiated modified product of Poria cocos peel triterpenoid, and D-gluconic acid-δ-lactone was (10~20) mL:(24~34) mg:(1~200) mg:(36~51) mg.
[0060] Based on the same inventive concept, the above-mentioned Poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing is used in the preparation of a drug for promoting skin wound healing; skin wounds include chronic, refractory wounds (such as diabetic foot ulcers, pressure ulcers). Furthermore, the above-mentioned Poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing is used to achieve time-specific, stage-specific repair, wherein: the hydrogel dressing containing a Poria cocos peel neutral triterpenoid solid dispersion with polyvinylpyrrolidone as a carrier is used in the preparation of a drug for inhibiting the inflammatory response in the early stage (0-5 days) of wound healing; the hydrogel dressing containing a Poria cocos peel neutral triterpenoid solid dispersion is used to inhibit the inflammatory response in the early stage (0-5 days) of wound healing; the hydrogel dressing containing a Poria cocos peel total triterpenoid solid dispersion with polyvinylpyrrolidone as a carrier is used in the preparation of a drug for... Applications of hydrogel dressings containing total triterpenoids from Poria cocos peel in promoting collagen synthesis and deposition during the proliferative phase (5-10 days) of wound healing; and applications of hydrogel dressings containing triterpenoid salts from Poria cocos peel in the preparation of drugs for promoting epithelial regeneration, angiogenesis, and tissue remodeling during the remodeling phase (7-14 days) of wound healing.
[0061] Furthermore, such as Figure 1As shown, it illustrates the complete process of extracting triterpenoid components from Poria cocos peel, preparing a modified product of Poria cocos peel—sodium alginate hydrogel dressing, and promoting wound healing; among which, Figure 1 A in the diagram describes the extraction of total triterpenoids (PCTT) from Poria cocos peel (the medicinal material on the left in the image) using solvent reflux. PCTT is then converted into two derivatives through a salt formation reaction: PCWT (neutral triterpenoids from Poria cocos peel) and PCNT (triterpene salts from Poria cocos peel). Figure 1 In section B, hydrogel dressings are prepared using PCTT / PCNT / PCWT as raw materials. Specifically, PCTT (or PCNT) is first mixed with PVP K30 at 60℃ to obtain a solid dispersion (such as PCTT / SD, PCNT / SD); after stirring steps such as "SA pre-swelling → adding CaCO3 → adding GDL (gluconolactone)," the corresponding hydrogel dressings (such as PCTT / SD / Gel, PCNT / SD / Gel, PCWT / Gel) are finally prepared. Figure 1 The mechanism by which hydrogel dressings promote wound healing is as follows: After hydrogel dressings are applied to wounds, they accelerate healing through the following processes: Modulation of the wound microenvironment: PCNT / SD / Gel significantly downregulated the mRNA expression of the early pro-inflammatory factor IL-6; PCTT / SD / Gel significantly upregulated the mRNA expression of collagen Iα2 chain (COL1α2); PCWT / Gel: significantly upregulated the mRNA expression of epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), driving epithelial regeneration and angiogenesis.
[0062] In summary, this invention addresses the technical challenge of achieving sequential therapeutic effects due to the strong hydrophobicity of Poria cocos peel triterpenes. It employs specific solid dispersion techniques (using polyvinylpyrrolidone K30 as a carrier, with a drug-to-carrier mass ratio of 1:4 to 1:12) or salt formation techniques to physicochemically modify the triterpenes, and then reacts them with sodium alginate solution via calcium ion exchange (Ca). 2+Cross-linking and compounding were used to construct a series of composite hydrogel dressings. These hydrogel dressings possess a three-dimensional porous network structure, high water content (≥90%), excellent blood compatibility (hemolysis rate <5%), and ideal swelling properties (equilibrium swelling rate ≥600%). The core inventive effect of this invention lies in the fact that three differentiated modified products of Poria cocos peel triterpenes (PCTT / SD, PCNT / SD, PCWT), obtained through different modification pathways, exhibit clear and complementary stage-specific therapeutic advantages in the complex wound healing process after being loaded into the same hydrogel system: PCNT / SD / Gel effectively regulates early inflammation and accelerates initial repair; PCTT / SD / Gel significantly promotes mid-stage collagen synthesis and deposition; and PCWT / Gel efficiently drives late-stage epithelialization, angiogenesis, and tissue remodeling. This invention achieves precise temporal control of the wound healing process, providing an innovative treatment strategy for chronic and difficult-to-heal wounds such as diabetic foot ulcers, and significantly enhancing the added value of Poria cocos peel by-products.
[0063] The following specific examples further illustrate the Poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing, its preparation method, and its application. The biomaterials used in the following examples are listed below to ensure reproducibility: Hematoxylin-eosin HE staining solution and Masson's staining solution were purchased from Wuhan Sewell Biotechnology Co., Ltd. (Wuhan, China); the enzyme-linked immunosorbent assay (ELISA) kits for interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-α (TNF-α) were purchased from Wuhan Elite Biotechnology Co., Ltd. (Wuhan, China). Real-time quantitative polymerase chain reaction (qRT-PCR) primers were synthesized by Shanghai Jierui Biotechnology Co., Ltd. (Shanghai, China). TRNzol Universal RNAReagent and FastKing cDNA first-strand synthesis kits were purchased from TIANGEN.
[0064] Example 1
[0065] This embodiment provides a method for preparing total triterpenoids (PCTT) from Poria cocos peel, including the following steps:
[0066] S1. Take dried Poria cocos peel, crush it, and accurately weigh 100g; add the crushed 100g of Poria cocos peel to 800 mL of 70% (v / v, volume concentration) ethanol aqueous solution, heat and reflux at 85℃ for 2 hours, filter, and obtain the first extract and residue.
[0067] S2. Add the residue back into 800 mL of 70% aqueous ethanol and heat under reflux at 85°C for 1 hour. Filter to obtain the second extract.
[0068] The first and second extracts were combined and concentrated under reduced pressure at 60°C to a paste. The paste was then dried in a vacuum drying oven at 50°C until constant weight, and ground to obtain a brown powder of total triterpenoids (PCTT) from Poria cocos peel.
[0069] Example 2
[0070] This embodiment provides a method for preparing Poria cocos peel triterpene salt (PCWT) and Poria cocos peel neutral triterpene compound (PCNT), including the following steps:
[0071] S1. Dissolve 3.0 g of PCTT prepared in Example 1 in 20 mL of anhydrous ethanol to prepare an ethanol solution of PCTT;
[0072] S2. Under magnetic stirring, the ethanol solution of PCTT was slowly added dropwise at a rate of 1 mL / min to 400 mL of 0.015 mol / L NaOH aqueous solution preheated to 80℃. After the addition was complete, the reaction was continued to be stirred at 80℃ for 2 hours. After the reaction was completed, the reaction solution was placed in a 40℃ water bath for vacuum rotary evaporation to completely remove the ethanol. After the remaining aqueous solution was cooled to room temperature, it was filtered with medium-speed filter paper, and the filter cake (at the same time, the filtrate was obtained) was collected. The cake was washed twice with a small amount of ice water (to obtain the washing liquid), and dried in a vacuum drying oven at 40℃ to constant weight to obtain a light yellow solid, which is the neutral triterpenoid compound of Poria cocos peel (PCNT). All the filtrates and washing liquids were combined, concentrated to a small volume under reduced pressure at 40℃, transferred to a petri dish, and dried in a vacuum drying oven at 40℃ to constant weight to obtain a yellowish-brown solid, which is the triterpene acid salt of Poria cocos peel (PCWT).
[0073] Example 3
[0074] This embodiment provides a method for preparing total triterpenoid solid dispersions and neutral triterpenoid solid dispersions from Poria cocos peel, specifically including:
[0075] S1. Resveratrol (Res, molecular formula C) 14 H 12O3 (CAS501-36-0, positive control), PCTT and PCNT samples (0.500 g each) prepared in Examples 1 and 2 were mixed uniformly with 4.500 g of polyvinylpyrrolidone K30 (PVP K30, drug-to-weight ratio 1:9) carrier material. Each mixture was transferred to a 250 mL beaker, 50 mL of anhydrous ethanol was added, and the mixture was sonicated for 20 minutes to dissolve completely. The beakers were placed in an 80°C water bath (light protection is required when preparing Res / SD), and the solvent was slowly evaporated by magnetic stirring until the system became a viscous semi-solid. The viscous substance was quickly scraped into a glass petri dish and dried in a 60°C vacuum drying oven for 24 hours until constant weight. The dried material was removed, ground into a fine powder using a mortar and pestle, and passed through an 80-mesh sieve to obtain white (Res / SD), dark brown (PCTT / SD, i.e., the solid dispersion of total triterpenes from Poria cocos peel with polyvinylpyrrolidone as a carrier mentioned above), and light brown (PCNT / SD, i.e., the solid dispersion of neutral triterpenes from Poria cocos peel with polyvinylpyrrolidone as a carrier mentioned above) solid dispersions of differentiated modified triterpenes from Poria cocos peel, respectively. These powders were then sealed and stored in a desiccator.
[0076] Performance characterization of PCTT, PCWT, PCTT / SD, and PCNT / SD in Examples 1-3
[0077] Determination of Triterpenoid Content by Vanillin-Glacial Acetic Acid-Perchloric Acid Colorimetric Method
[0078] Take 0.3 mL of ursolic acid (UA, molecular formula C) with a concentration of 208 μg / mL. 30 H 48 The uric acid standard solution (CAS No. 77-52-1) was placed in a test tube and evaporated to dryness in a 70°C water bath to remove methanol. The solution was then cooled to room temperature. Next, 0.2 mL of freshly prepared 5% vanillin-acetic acid solution and 0.8 mL of perchloric acid were added, and the mixture was thoroughly shaken and incubated in a 70°C water bath for 15 min. The mixture was then cooled to room temperature in an ice-water bath, 5 mL of acetic acid was added, and the mixture was shaken again and allowed to stand for 10 minutes. The blank control was prepared by replacing the uric acid standard solution with 0.3 mL of methanol, following the same steps. The absorption spectra were recorded using a spectrophotometer in the wavelength range of 400-600 nm (resolution: 10.0 nm). The ordinate represents absorbance, and the abscissa represents wavelength.
[0079] To construct a standard curve, 0.1 mL, 0.2 mL, 0.3 mL, 0.4 mL, and 0.5 mL of ursolic acid standard solution with a concentration of 208 μg / mL were respectively pipetted, and the absorbance at the wavelength of maximum absorption was measured according to the method described above. A standard curve was plotted with ursolic acid concentration on the x-axis and absorbance on the y-axis, and the linear regression equation was calculated.
[0080] For sample analysis, 4 mg PCTT, 2 mg PCNT, 10 mg PCWT, 100 mg PCTT / SD, and 50 mg PCNT / SD were accurately weighed into 50 mL volumetric flasks, diluted to the mark with methanol, and thoroughly mixed by vortexing to prepare test solutions. 1 mL of each test solution was evaporated to dryness in a 70°C water bath, cooled to room temperature, and then vanillin-glacial acetic acid-perchloric acid reagent was added according to the standard solution treatment method. The absorbance at the maximum absorption wavelength was measured, and the total triterpenoid content was calculated using a linear regression equation, expressed as ursolic acid equivalents.
[0081] Determination of resveratrol content
[0082] Take 0.5 mL, 1 mL, 1.5 mL, 2 mL, 2.5 mL, 3 mL, and 3.5 mL of a 61 μg / mL Res reference solution and place them in 50 mL volumetric flasks, then dilute to volume. Measure the absorbance at 306 nm. Plot a standard curve with concentration on the x-axis and peak area on the y-axis, and calculate the regression equation. Then, accurately weigh 2 mg of Res / SD into a 50 mL volumetric flask, add methanol to dilute to volume, and prepare a test solution with a concentration of 0.04 mg / mL. Measure the absorbance using the method described above and calculate the content.
[0083] Figure 2 A is the pH change curve during the salt formation reaction of total terpenoids (PCTT) in Poria cocos peel with NaOH; B is the full-wavelength absorption spectrum (400~700 nm) of ursolic acid (UA) methanol solution; C is the standard curve of ursolic acid concentration versus absorbance (detection wavelength: 548 nm); D is the standard curve of resveratrol concentration versus absorbance (detection wavelength: 306 nm).
[0084] from Figure 2 As shown in Figure (A), the pH value of the reaction system decreased significantly with the gradual addition of PCTT ethanol solution. When 5 mL of PCTT ethanol solution was added, the pH stabilized, indicating that the salt formation reaction was essentially complete. Further addition of PCTT ethanol solution resulted in a continued slight decrease in pH, confirming the presence of unreacted free PCTT in the system. Figure 2 (As shown in A).
[0085] Full wavelength scan of ursolic acid (UA) methanol solution in the 400–600 nm wavelength range ( Figure 2 Image B) shows that its maximum absorption peak is located at 548 nm, therefore this wavelength was selected as the detection wavelength. The linear regression equation for the ursolic acid standard curve is Y = 0.0441X - 0.0425, and the correlation coefficient R0 is [missing value]. 2= 0.9990, indicating a good linear relationship in the concentration range of 3.467-17.333 μg / mL. Figure 2 (C). According to the standard curve, the contents of triterpenoids in the PCTT, PCNT, PCWT, PCTT / SD, and PCNT / SD samples were 45.78%, 71.37%, 23.13%, 2.51%, and 4.67%, respectively.
[0086] For resveratrol (Res), the linear regression equation for the standard curve is Y = 0.1220X - 0.0034, R0 2 =0.9997, indicating a reliable linear relationship in the range of 0.061~4.270 μg / mL. Figure 2 (D). The resveratrol content in the Res / SD formulation was determined to be 9.59% using this standard curve.
[0087] Figure 3 The FT-IR spectra of PCTT, PCNT, and PCWT prepared in Examples 1-2 are shown. Figure 4 A represents the FT-IR spectrum of PVP K30, PCTT, PCTT / SD, and PCTT+PVP K30 physical mixtures from Examples 1-3 (i.e., directly mixing 0.5g PCTT with 4.500g PVP K30); B represents the FT-IR spectrum of PVP K30, PCNT, PCNT / SD, and PCNT+PVP K30 physical mixtures from Examples 1-3 (i.e., directly mixing 0.5g PCNT with 4.500g PVP K30); C represents the FT-IR spectrum of PVP K30, Res, Res / SD, and Res+PVP K30 physical mixtures (i.e., directly mixing 0.5g Res with 4.500g PVP K30).
[0088] like Figures 3-4 As shown, PCTT, PCNT, and PCWT exhibit typical CH3CH2 symmetric / asymmetric stretching vibrations (2960-2850 cm⁻¹), respectively. -1 C=O stretching vibration (1500-1800 cm) -1 ) and CH / OH vibration (1500-1200 cm) -1 Carboxylic acids typically exist as dimers due to hydrogen bonding, and their free OC=O stretching vibration peak is located at 1760 cm⁻¹. -1 The dimer stretching vibration peak is located at 1710 cm⁻¹. -1 PCTT at 1701 cm -1 An absorption peak appears at 1717 cm⁻¹, while PCNT shows an absorption peak at 1717 cm⁻¹. -1The presence of a peak at 1375 cm⁻¹ confirms that both PCTT and PCNT contain the OC=O group. PCTT and PCNT show a peak at 1375 cm⁻¹. -1 The peak at 1200-900 cm⁻¹ is attributed to the triterpenoid characteristic group CH₂=CH-CH₃, while the peak at 1200-900 cm⁻¹ is attributed to the triterpenoid characteristic group CH₂=CH-CH₃. -1 The peak values within the range correspond to the CO bending vibration, -CH2 bending vibration, CC stretching vibration, and CO stretching vibration, respectively. Compared with PCTT, the intensity of the characteristic peaks in PCNT is significantly enhanced, indicating that PCNT has a higher degree of crystallinity.
[0089] Carboxylate ions at 1400 cm -1 It exhibits symmetrical stretching vibration at 1500-1610 cm. -1 The PCWT exhibits reverse symmetrical stretching vibration at 1557 cm⁻¹. -1 and 1400 cm -1 The presence of an absorption peak at [value missing] confirms the formation of the carboxylate ion, while such peaks were not observed in PCTT or PCNT. These results indicate a significant change in the OC=O absorption peak after PCTT salting, confirming the successful synthesis of water-soluble Poria cocos peel triterpenoid salts.
[0090] The PVP K30 is 3419 cm high. -1 and 1648 cm -1 The -OH and C=O stretching vibration peaks are observed. After physical mixing with PCTT or forming a solid dispersion, the -OH stretching peak shifts to the right, while the C=O peak remains consistent with that of pure PVP K30. Figure 4 (A) indicates that potential hydrogen bonding interactions exist between PCTT and PVP K30 even in physical mixtures. For PCTT and PVP K30 (… Figure 4 In the PCNT / SD system (B), the -OH stretching peak increased from 3291 cm⁻¹. -1 Move to ~3400 cm -1 The C=O peak is at 1717 cm⁻¹ -1 Moved to 1652 cm -1 Furthermore, the strength was significantly enhanced, further confirming the hydrogen bonding effect and amorphous dispersion of PCNT in PVP K30.
[0091] Res at 3184 cm -1 (-OH), 1605 cm -1 / 1584 cm -1 (C=C), 1381 cm -1 (CO) and 964 cm -1 Characteristic peaks are observed at (trans-olefin). In a Res+PVP K30 physical mixture ( Figure 4In the Res / SD system, the characteristic peaks of Res and PVP K30 completely overlap. In the Res / SD system, the -OH peak shifts to 3390 cm⁻¹. -1 The weakening or disappearance of some Res characteristic peaks indicates that there is an intermolecular interaction between Res and PVP K30.
[0092] Figure 5 In Figure A, the XRD patterns of PVP K30, PCTT, PCTT / SD, and the physical mixture of PCTT+PVP K30 in Example 1 are shown. Figure 5 In the image, B represents the XRD patterns of PVP K30, PCNT, PCNT / SD, and the physical mixture of PCNT+PVP K30 in Example 1. Figure 5 In the middle, C represents the XRD patterns of physical mixtures of PVP K30, Res, Res / SD, and Res+PVP K30.
[0093] from Figure 5 As can be seen from the XRD diffraction pattern of PCTT ( Figure 5 (A) exhibits relatively broad and distinct diffraction peaks at 14.97° and 17.24°, indicating that its crystallinity is low but still identifiable; PCNT ( Figure 5 (B) exhibits sharp diffraction peaks at 5.41°, 7.71°, 13.30°, 15.54°, and 17.30°, while Res ( Figure 5 The sharp peaks at 6.64°, 13.36°, 16.42°, 19.21°, 22.39°, 23.66°, and 28.29° in PCNT and Res confirm their high crystallinity. In contrast, PVPK30 exhibits broad amorphous peaks at 11.35° and 20.54°.
[0094] The diffraction peaks of the PCTT+PVP K30 physical mixture were significantly weakened but still detectable, indicating that some crystalline PCTT was retained. Similarly, the Res+PVP K30 physical mixture exhibited both the amorphous characteristics of PVP K30 and the residual crystalline peaks of Res. However, in the XRD patterns of PCTT / SD, PCNT / SD, and Res / SD, all characteristic crystalline peaks of PCTT, PCNT, and Res disappeared. These results confirm that PCTT, PCNT, and Res are completely dispersed amorphously in PVP K30, consistent with the FT-IR analysis results.
[0095] Figure 6 This is a scanning electron microscope (SEM) image of the PCNT / SD from Example 3. From... Figure 6As can be seen from the results, the solid dispersion was successfully prepared and PCNT / SD exhibited an amorphous bulk structure, indicating that the triterpenoid compound / resin was completely dispersed in PVP K30 in an amorphous state, which is consistent with the XRD results.
[0096] Example 4
[0097] This embodiment provides a method for preparing a hydrogel dressing made from a modified product of Poria cocos peel triterpenoids – sodium alginate, comprising the following steps:
[0098] S1. Preparation of sodium alginate (SA) aqueous solution: Accurately weigh 2.0 g of SA powder, add 98 mL of ultrapure water, let it stand at room temperature to swell for 1 hour, then place it in a 50℃ water bath and stir magnetically for 30 minutes until completely dissolved to obtain a 2.0% (w / v) sodium alginate aqueous solution. Degas it by sonication for 30 minutes and set aside.
[0099] S2. Prepare five hydrogel dressings according to the formulations in Table 1. Taking the preparation of PCTT / SD / Gel as an example: Take 10 mL of sodium alginate aqueous solution from S1 into a beaker, add 24 mg of calcium carbonate (CaCO3), and stir at 50°C for 30 minutes to ensure thorough dispersion;
[0100] Add 100 mg of the PCTT / SD prepared in Example 3 and continue stirring for 30 minutes until completely dissolved and dispersed (to obtain a pregel solution); then add 36 mg of D-glucono-δ-lactone (GDL), stir for 30 seconds, and then sonicate the mixture for 10 minutes to remove air bubbles; subsequently, quickly inject the solution into a silicone mold with an inner diameter of 35 mm and allow it to stand horizontally at room temperature; after standing for 1 hour, a complete circular PCTT / SD / Gel hydrogel dressing is obtained. Other formulations are prepared according to the proportions in Table 1.
[0101] Table 1 - Formulation composition of five types of hydrogel dressings
[0102]
[0103] Performance characterization of hydrogel dressing in Example 4
[0104] Gel and Res / SD / Gel were white, with a gelation time of 12.5 min; PCTT / SD / Gel were dark brown, with a gelation time of 8.5 min; PCNT / SD / Gel were light brown, with a gelation time of 8.5 min; and PCWT / Gel were yellowish-brown, with a gelation time of 12 min. The gelation time was measured as follows: GDL was added to a transparent glass vial containing the pre-gelled solution of solid dispersions with different drug loading ratios prepared according to Example 4. Timing was started immediately after adding the GDL and the vial was shaken well. The vial was placed horizontally on a 25°C constant temperature table. Every 30 seconds, the vial was tilted to an 80° angle with the horizontal plane and held for 5 seconds, observing the liquid level. The time when the liquid level completely stopped flowing within 5 seconds was recorded as the gelation endpoint. Each sample was measured in triplicate, and the average value was taken.
[0105] Figure 7 Scanning electron microscope image of PCTT / SD / Gel; Figure 8 Scanning electron microscope image of PCNT / SD / Gel; Figure 9 This is a scanning electron microscope image of PCWT / Gel.
[0106] from Figures 7-9 As can be seen, scanning electron microscopy confirmed the successful formation of the hydrogels, with all hydrogels exhibiting a typical porous network structure. The PCTT / SD / Gel and PCNT / SD / Gel samples showed uneven pore size distribution, while PCWT / Gel exhibited a relatively uniform pore structure. This highly developed porous structure endows the material with a large specific surface area and porosity, creating an ideal microenvironment for cell adhesion, proliferation, and migration (especially fibroblasts). Furthermore, its interconnected channel structure promotes efficient transport of nutrients and oxygen, combined with excellent exudate absorption capacity, accelerating the wound healing process.
[0107] Figure 10 Fourier transform infrared (FT-IR) spectra of SA, Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel Figure 10 (A) and moisture content ( Figure 10 (B)
[0108] The moisture content testing method was as follows: Each hydrogel dressing (Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel) was accurately weighed, and its wet weight was recorded as W2. Subsequently, the hydrogels were freeze-dried for 48 hours using an FDU-1110 freeze dryer (EYELA, Japan), and the dried mass was recorded as W1. The moisture content calculation formula is as follows: .
[0109] The high water absorption and swelling capacity of hydrogels is closely related to their internal three-dimensional network structure and hydrophilic groups (such as -COOH and -OH), which drive the water absorption and swelling process. Figure 10 FT-IR analysis showed that pure SA at 3231 cm⁻¹ -1 The -OH stretching vibration peak is observed at 1593 cm⁻¹. -1 and 1405 cm -1 The peaks at 1023 cm⁻¹ exhibit asymmetric / symmetric vibrations of the carboxyl group. -1 A CO stretching vibration peak is observed at this location. Among all five hydrogel formulations, the asymmetric / symmetric vibration peak intensity of the carboxyl group is relatively weak, which is due to the Ca... 2+ This is due to the "chelation" with the carboxyl group, confirming the interaction between SA and Ca. 2+ Cross-linking reaction between them.
[0110] from Figure 10 As shown in Figure B, the water contents of Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel were 97.61%, 97.51%, 92.33%, 96.08%, and 96.64%, respectively. Compared with the Gel and Res / SD / Gel groups, the water content of the triterpenoid-loaded hydrogels was significantly reduced (P < 0.01), with PCWT / Gel exhibiting the highest water content among the three Poria cocos peel triterpenoid hydrogels. This reduction is attributed to the introduction of triterpenoids, which increases the hydrogel network density and reduces pore volume, thereby affecting water absorption and retention capacity. However, the water content of all hydrogels was significantly higher than that of normal skin (69.59%), meeting the basic requirements for clinical wound dressings and providing an ideal moist environment for wound healing.
[0111] Figure 11 Visual observation of the color of the supernatant after hemolysis tests with different hydrogel dressings (positive control: ultrapure water; negative control: phosphate-buffered saline PBS) results. Figure 11 (A) and quantitative analysis ( Figure 11(B) The hemocompatibility of the hydrogel was assessed through an in vitro hemolysis experiment. Specifically, fresh rat whole blood was centrifuged at 3000 rpm for 15 min using a KDC-140HR high-speed refrigerated centrifuge. Red blood cell (RBC) pellets were collected, washed three times with phosphate-buffered saline (PBS, pH 7.4), and diluted to a 2% (v / v) red blood cell suspension. Each hydrogel sample was added to 0.7 mL of the diluted red blood cell suspension. PBS and ultrapure water were used as negative and positive controls, respectively. After incubation at 37℃ for 1 h, the sample was centrifuged at 3000 rpm for 10 min. The absorbance of the supernatant at 540 nm was measured within 10 minutes using an N60 Implen ultraviolet-visible spectrophotometer. The hemolysis rate was calculated using the following formula: In the formula, As, An, and Ap are the absorbance values of the sample, negative control, and positive control, respectively.
[0112] like Figure 11 As shown, the positive control group (ultrapure water) appeared red due to severe hemolysis, while the supernatants of other groups were orange-yellow. Quantitative analysis showed that the hemolysis rates of Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel were 1.29%, 2.06%, 4.00%, 2.45%, and 3.84%, respectively, all below the international safety threshold of 5%. These results indicate that all hydrogel formulations have good blood compatibility. Among the three triterpenoid drug-loaded hydrogels, PCNT / SD / Gel had the lowest hemolysis rate, indicating superior biocompatibility in applications involving direct blood contact, such as transdermal drug delivery. This advantage may be related to its uniform and dense network structure and smoother surface properties, which reduce erythrocyte damage.
[0113] Figure 12 The swelling rate of different hydrogel dressings in PBS (pH=7.4, 37℃) within 72 h was measured. Specifically, the swelling rate test method was as follows: the freeze-dried hydrogel dressing was weighed (dry weight, W_d) and immersed in PBS (pH 7.4) at 37℃. It was removed at predetermined time points (1, 2, 4, 8, 12, 24, 48 and 72 h), the surface moisture was blotted with filter paper and then weighed (wet weight, W_s). The swelling rate (SR) was calculated using the formula: SR (%) = [(W_s - W_d) / W_d] × 100%.
[0114] from Figure 12It can be seen that the swelling rate of the hydrogels increases with time and reaches equilibrium at 24 h. At equilibrium, the swelling rates of Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel are 2606.67%, 2382.59%, 669.78%, 938.71%, and 1184.15%, respectively. Despite the differences in swelling capacity, all formulations exhibit excellent wound exudate absorption capacity, meeting the standards for ideal dressings. Among the triterpenoid drug-loaded hydrogels, PCWT / Gel exhibits the highest swelling rate, which may be related to its unique network structure formed through the introduction of PCWT.
[0115] Figure 13 A, B, and C are frequency dependence curves of storage modulus (G') and loss modulus (G") of gel, triterpenoid drug-loaded hydrogel dressing, and Res / SD / Gel system; frequency scanning tests were performed using a rotational rheometer (1% strain, 1-100 rad / s frequency, 37℃).
[0116] from Figure 13 As can be seen, the storage modulus (G') of all hydrogel dressings is higher than the loss modulus (G") across the entire frequency range, exhibiting typical viscoelastic behavior dominated by elastic solids. This indicates that they have a stable network structure, which can maintain the shape of the dressing and withstand certain external forces.
[0117] Example 5
[0118] This embodiment further conducts gradient experiments on drug loading ratios (1:4 to 1:12, i.e., the mass ratio of PCTT to PVP K30). Specifically, the amount of PCTT was fixed at 0.5g, and it was mixed with 2.0g, 3.0g, 4.5g, and 6.0g of PVP K30 (corresponding to drug loading ratios of 1:4, 1:6, 1:9, and 1:12, respectively) to prepare Poria cocos total triterpenoid solid dispersions PCTT / SD according to the method in Example 3. The dissolution rate of PCTT in each solid dispersion was measured (in pH 7.4 PBS, 60 minutes). The Poria cocos total triterpenoid solid dispersions PCTT / SD prepared with different drug loading ratios were used to prepare hydrogel dressings PCTT / SD / Gel according to the method in Example 4. The gelation time, mechanical strength (storage modulus G'), and in vitro cumulative drug release rate (72 hours) were measured. The results are shown in Table 2.
[0119] Table 2 - Properties of solid dispersions and their hydrogels prepared with different drug loading ratios
[0120]
[0121] As shown in Table 2, within the range of 1:4 to 1:12, as the carrier ratio increases, both drug dissolution and in vitro release rate significantly improve (compared to the active pharmaceutical ingredient), while the hydrogel still maintains acceptable gelation time and sufficient mechanical strength. Below 1:4, drug crystallization is evident, and release performance declines; above 1:12, the performance improvement is no longer significant, and the volume of the dressing per unit dose is excessively large. Therefore, 1:4 to 1:12 is a reasonable range for achieving the desired technical effect, with 1:9 achieving the best balance in all performance aspects.
[0122] In vivo animal experiments were conducted to verify the specific repair function of the hydrogel (using the hydrogel excipient prepared with a drug loading ratio of 1:9 in Example 4). The study also investigated the wound-healing effect of the hydrogel.
[0123] Internal wound healing assessment
[0124] Male Sprague-Dawley (SD) rats (200 g) were purchased from Hunan SJA Laboratory Animal Co., Ltd. (SPF grade, Changsha, China). All animal experiments and procedures were approved by the Animal Ethics Committee of Hubei University of Traditional Chinese Medicine.
[0125] Fifty-six SD rats were randomly divided into seven groups (n=8 per group): (1) Control group (no treatment); (2) Model group (wound + saline); (3) Gel; (4) Res / SD / Gel group (positive control); (5) PCTT / SD / Gel group; (6) PCNT / SD / Gel group; (7) PCWT / Gel group. Rats were anesthetized with isoflurane, and two full-thickness skin defects with a diameter of approximately 11 mm were prepared on the back.
[0126] The wounds of the normal and model groups were cleaned daily with physiological saline. The Gel, Res / SD / Gel, PCTT / SD / Gel, PCNT / SD / Gel, and PCWT / Gel groups were treated daily for 10 consecutive days with the corresponding hydrogel formulation. The body weight of each rat was recorded on days 0, 3, 5, 7, and 10 after administration, and the wounds were digitally photographed. The images were analyzed using ImageJ software, and the wound area was calculated using a scale calibration. Each wound was measured three times, and the average value was taken to calculate the wound healing rate: Healing rate (%) = [(Area on day 0 - Area on day n) / Area on day 0] × 100%.
[0127] Rat organ index determination
[0128] On day 10 after modeling, rats in each group were euthanized under anesthesia and dissected. The spleen and thymus were removed, blotted dry with filter paper, and weighed accurately. The spleen index and thymus index were calculated using the following formulas: In the formula, m and M are the organ weight and rat body weight, respectively.
[0129] Histological and morphological analysis
[0130] On postoperative days 3, 7, and 10, wound tissue samples (approximately 1 cm × 1 cm) were harvested and fixed in 4% paraformaldehyde solution for 24 hours. After paraffin embedding, the fixed tissue was sectioned to a thickness of 5 mm and stained using hematoxylin-eosin (H&E) and Masson's trichrome staining kit. The stained sections were observed and imaged using a JSM-6510LV scanning electron microscope (JEOL Ltd.) to assess pathological morphological changes, including epithelialization reversion, granulation tissue formation, and collagen deposition.
[0131] Enzyme-linked immunosorbent assay (ELISA)
[0132] On day 10 after modeling, blood samples were collected from the abdominal aorta of anesthetized rats, and serum was separated by centrifugation at 3000 rpm / min for 15 min at 4°C. The concentrations of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10) in the serum were detected strictly following the manufacturer's instructions of the ELISA kit (Elabscience Biotechnology Co., Ltd., China).
[0133] Real-time quantitative polymerase chain reaction (qRT-PCR)
[0134] On day 10 after modeling, total RNA was extracted from wound tissue using TRNzol Universal RNA Reagent (TIANGEN, China) according to the kit instructions. RNA purity and concentration were verified using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, USA). Using 1 μg of total RNA as a template, cDNA was synthesized using the FastKing cDNA First-Strand Synthesis Kit (TIANGEN, China). The mRNA expression levels of inflammatory factors (TNF-α, IL-6), collagen synthesis-related factors (COL1α2, type I collagen α2), and growth factors (epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), and fibroblast growth factor-2 (FGF-2)) were quantitatively detected by qRT-PCR.
[0135] Real-time quantitative PCR was performed in a 20 μL system: 10 μL SYBR Green Supermix (2x), 0.6 μL forward primer (10 μmol / L), 0.6 μL reverse primer (10 μmol / L), 50 ng cDNA template, and ddH2O to make up the volume. The reaction conditions were as follows: 95℃ denaturation for 2 min; 40 cycles (95℃ denaturation for 5 s, 60℃ annealing for 10 s, 72℃ extension for 15 s); melting curve analysis was performed to verify primer specificity. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as an internal control gene for normalization. The relative mRNA expression level was determined by 2... -ΔΔCt The primer sequences were calculated using the method described in Table 3.
[0136] Table 3 - Primer sequences for each factor
[0137]
[0138] Hydrogel dressings promote wound healing
[0139] Figure 14 The changes in body weight of rats in each group within 10 days after wound formation; among them, Figure 14 In the diagram, the blank hydrogel group corresponds to the Gel group, the resveratrol group corresponds to the Res / SD / Gel group, the total triterpenoids group of Poria cocos peel corresponds to the PCTT / SD / Gel group, the neutral triterpenoids group of Poria cocos peel corresponds to the PCNT / SD / Gel group, and the triterpene acid salt group of Poria cocos peel represents the PCWT / Gel group. Figure 15 A~B represent the spleen index of rats on day 10 after wound formation. Figure 15 (A) and thymus index ( Figure 15 (Middle B) Figure 16 Representative images of wound healing at different time points (days 0, 3, 5, 7, and 10) in a full-thickness skin defect model; Figure 17 The wound contraction rate at each time point is represented by different treatment groups. Data are expressed as mean ± standard deviation (mean ± SD) (*P < 0.05, **P < 0.01, n=6).
[0140] From day 0 to day 3 after modeling, all groups of rats experienced a temporary decrease in body weight, mainly attributed to trauma-induced stress response (reduced food intake and restricted activity). From day 5 onwards, the body weight of rats in all groups showed a stable upward trend, indicating a gradual recovery of physiological function. Figure 14 Throughout the observation period, there were no significant differences in body weight changes among the groups (P>0.05), indicating that different treatments had similar effects on the metabolic state of rats. On day 10 after modeling, there were no statistically significant differences in spleen index and thymus index between the treatment groups and the model group. Figure 15(A and B) indicates that the hydrogel formulation has no significant adverse effects on the immune organs of rats.
[0141] from Figures 16-17 Macroscopic healing processes showed that all treatment groups healed faster than the model group. On days 3-5 (inflammation / early proliferative phase): the wounds in the model and Gel groups were moist and significantly red and swollen; the wounds in the PCNT / SD / Gel group dried quickly, forming a thin scab, with the least redness and swelling, demonstrating its outstanding early anti-inflammatory and astringent effects. On day 7 (proliferative phase): the wounds in the PCTT / SD / Gel group showed significant contraction, with newly formed tissue appearing a healthy pink color and the granulation tissue filling being the most complete. On day 10 (remodeling phase): the wounds in the PCWT / Gel group were almost completely closed, with smooth, even new epithelium, the color closest to the surrounding normal skin, and minimal scarring, showing the best repair quality. The Res / SD / Gel group was also effective, but the smoothness of healing was slightly inferior to the PCWT / Gel group.
[0142] Histological analysis
[0143] Figure 18 Image A shows H&E staining of wound tissue on days 3, 7, and 10 after drug administration (scale bar: 100 μm). Image B shows Masson's trichrome staining of wound tissue on days 3, 7, and 10 after drug administration (collagen fibers appear blue; scale bar: 100 μm). H&E and Masson's staining were performed on wound tissue on days 3, 7, and 10 after drug administration to further evaluate wound healing. Figure 19 A, B).
[0144] H&E staining results: On day 10, all drug-loaded treatment groups achieved complete epithelialization. However, the PCWT / Gel group showed the most complete newly formed epidermal structure, with clear skin papillae and obvious regeneration of skin appendages such as hair follicles, which is a hallmark of high-quality healing. The PCNT / SD / Gel group showed the least early inflammatory cell infiltration. Masson staining results: From day 3 onwards, collagen deposition was greater in the three Poria cocos triterpenoid treatment groups than in the control group. On day 10, the PCTT / SD / Gel group had the richest, thickest, and most tightly and orderly arranged collagen fibers, confirming its strong ability to promote collagen synthesis and maturation.
[0145] Analysis of wound healing mechanism
[0146] Figure 19 In Figure A, the ELISA result shows the level of interleukin-10 (IL-10) in the wound tissue on day 10. Figure 19 B is IL-6. Figure 20 In the diagram, A represents tumor necrosis factor-α (TNF-α), and B represents COL1α2. Figure 21 For EGF, Figure 22In the table, A represents the relative mRNA expression levels of VEGF and B represents the relative mRNA expression levels of FGF-2 in wound tissue on day 10 (normalized using GAPDH as an internal reference). Data are expressed as mean ± standard deviation (*P < 0.05, **P < 0.01, n=6).
[0147] from Figures 19-22 As can be seen from the ELISA analysis of inflammatory cytokines, the level of the anti-inflammatory factor IL-10 in the wound tissue of the PCWT / Gel group was significantly higher than that of all other groups (p<0.01), explaining its superior ability to regulate inflammation and remodel tissue. Figure 19 RT-PCR analysis of key gene expression: PCNT / SD / Gel group: significantly downregulated mRNA expression of early pro-inflammatory factor IL-6 (p<0.01 vs model group), consistent with its macroscopic and histological early anti-inflammatory performance (A); Figure 19 In the B group (PCTT / SD / Gel group), the mRNA expression of collagen Iα2 chain (COL1α2) was significantly upregulated (p<0.01), directly demonstrating its molecular basis in promoting collagen synthesis. Figure 20 In the PCWT / Gel group (B group), the mRNA expression of epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) was significantly upregulated (p<0.05), driving epithelial regeneration and angiogenesis. Figure 21 , Figure 22 (A)
[0148] The above embodiments fully demonstrate that the different modified products of the present invention endow the hydrogel with clear differentiation stage-specific repair functions. PCNT / SD / Gel, PCTT / SD / Gel and PCWT / Gel exert superior therapeutic effects in the inflammatory phase, proliferative phase and remodeling phase, respectively. Together, they constitute a potential, intelligent time-series treatment plan.
[0149] The above are merely preferred embodiments of this application, and only specifically describe the technical principles of this application. These descriptions are only for explaining the principles of this application and should not be construed as limiting the scope of protection of this application in any way.
Claims
1. A modified product of Poria cocos peel triterpenoids with stage-specific repair function - sodium alginate hydrogel dressing, characterized in that, include: A sodium alginate hydrogel matrix with a three-dimensional porous network structure, and a poria cocos peel triterpenoid modified product dispersed in the sodium alginate hydrogel matrix; The modified triterpenoid products of Poria cocos peel are: a solid dispersion of total triterpenoids of Poria cocos peel with polyvinylpyrrolidone as a carrier, a solid dispersion of neutral triterpenoids of Poria cocos peel with polyvinylpyrrolidone as a carrier, and a triterpene acid salt of Poria cocos peel. The method for preparing the solid dispersion of total triterpenoids from Poria cocos peel using polyvinylpyrrolidone as a carrier is as follows: Poria cocos peel was mixed with an alcohol solvent and heated under reflux to extract the extract. The extract was then concentrated and dried to obtain total triterpenoids from Poria cocos peel. After mixing the total triterpenoids of Poria cocos peel with polyvinylpyrrolidone, an alcohol solvent was added, and the mixture was continued. After heating to evaporate the alcohol solvent, the mixture was dried to obtain a solid dispersion of total triterpenoids of Poria cocos peel with polyvinylpyrrolidone as the carrier. The preparation method of the neutral triterpenoid solid dispersion of Poria cocos peel using polyvinylpyrrolidone as a carrier is as follows: An alcoholic solution of total triterpenoids from Poria cocos peel was added dropwise to an aqueous solution of alkali metal hydroxide. The reaction was carried out, and the alcohol was removed by vacuum distillation to obtain a concentrated aqueous solution. After filtering the concentrated aqueous solution, a precipitate was obtained, which was the neutral triterpenoid compound of Poria cocos peel. After mixing neutral triterpenoids from Poria cocos peel with polyvinylpyrrolidone, an alcohol solvent was added, and the mixture was continued. After heating to evaporate the alcohol solvent, the mixture was dried to obtain a solid dispersion of neutral triterpenoids from Poria cocos peel with polyvinylpyrrolidone as the carrier. The preparation method of the poria cocos peel triterpene salt is as follows: An alcoholic solution of total triterpenoids from Poria cocos peel was added dropwise to an aqueous solution of alkali metal hydroxide. The reaction was carried out, and the alcohol was removed by vacuum distillation to obtain a concentrated aqueous solution. The concentrated aqueous solution was filtered and the filtrate was collected. The filtrate was then concentrated and dried to obtain Poria cocos peel triterpenic acid salt.
2. The poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in claim 1, characterized in that, The mass ratio of total triterpenoids in Poria cocos peel to polyvinylpyrrolidone in the solid dispersion of Poria cocos peel using polyvinylpyrrolidone as a carrier is 1:(4~12). In the neutral triterpenoid solid dispersion of Poria cocos peel with polyvinylpyrrolidone as the carrier, the mass ratio of neutral triterpenoid compounds of Poria cocos peel to polyvinylpyrrolidone is 1:(4~12).
3. The poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in claim 2, characterized in that, The mass ratio of total triterpenoids in Poria cocos peel to polyvinylpyrrolidone is 1:9; The mass ratio of the neutral triterpenoid compound in the poria cocos peel to polyvinylpyrrolidone is 1:
9.
4. The poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in claim 1, characterized in that, The sodium alginate hydrogel matrix is cross-linked with sodium alginate, calcium ion source and D-gluconic acid-δ-lactone.
5. The poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in claim 4, characterized in that, The calcium ion source is calcium carbonate; The alkali metal hydroxide is sodium hydroxide.
6. A method for preparing a hydrogel dressing of Poria cocos peel triterpenoid modified product-sodium alginate as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Sodium alginate was dissolved in water to form a solution, a calcium ion source was added, and the mixture was stirred to obtain a pre-gel solution. Add the poria cocos peel triterpenoid modified product to the pregel solution, stir, add D-gluconic acid-δ-lactone, continue stirring, and after ultrasonic degassing, obtain the mixture; The mixture was allowed to stand and crosslink to obtain a modified product of Poria cocos peel, sodium alginate hydrogel dressing.
7. The preparation method of the poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in claim 6, characterized in that, Sodium alginate is dissolved in water to form a sodium alginate solution with a mass fraction of 1-5%.
8. The use of a poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing as described in any one of claims 1 to 5, or a poria cocos peel triterpenoid modified product-sodium alginate hydrogel dressing prepared by the preparation method described in any one of claims 6 to 7, in the preparation of a drug for promoting skin wound healing.
Citation Information
Patent Citations
Method for preparing hydrogel surgical dressing and application of hydrogel surgical dressing
CN108785738A
Probiotic antibacterial gel dressing and preparation method thereof
CN118217450A